Desempenho operacional e custos do transporte florestal rodoviário em região montanhosa - Lachini, Edson (2015)
Within the forest sector transportation is one of the most costly activities, representing the most important element of logistics costs in most companies. The organization and rationalization of the forest transport operations, may represent a great resource savings for companies in the sector, and thus increase operational efficiency. This research was conducted in wood harvesting operational areas belonging to Jomadeiras company in the municipality of Domingos Martins, in the mountainous region of the Holy Spirit, and to analyze the technical factors and wood forest road transport costs. The study identified and assessed the factors that influence the timber transport system, evaluated the operational efficiency and finally analyzed the road transport costs. We evaluated the operations belonging to the forest transportation process, among them the operational average speed, operational factors of timber transport and analysis of the costs within the fleet of the company. The vehicles used were three models of trucks. With the research was possible to know in more detail the transportation system adopted by the company, identifying the main problems and proposing improvements to the transport activities are optimized. According to the analysis of the results of the operating time, the truck A showed the best results for mechanical availability and operational efficiency with 93.23 and 83.86%, respectively. The activities that most represented the operating times were the stops for meals (average of 18.30% of the total time), loading in the field (average of 20.04% of the total time), stops time (average of 79.4% of unproductive time) and maintenance (average of 11.48% of the total time). Regarding cost analysis, it was concluded that the truck B showed the best results in economic terms (5.53 R$ km). The truck was the one with the largest timber shipping cost (7.64 R$/km) in the field transfer to the sawmill.